2020
DOI: 10.1097/aog.0000000000004138
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Vacuum-Induced Hemorrhage-Control Device for Rapid Treatment of Postpartum Hemorrhage

Abstract: Intrauterine vacuum-induced hemorrhage control may provide an effective treatment option for postpartum hemorrhage that has the potential to prevent severe maternal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 18 publications
3
44
1
Order By: Relevance
“…A subsequent multicenter study of 106 women with uterine atony treated with this device reported a treatment success rate of 94%. 9 The findings of our observational study are in line with these results, showing a success rate of 86% in women with uterine atony in the overall study period and even 100% in women with uterine atony in the latter 2 years. However, in contrast to the latter study, we did not use vacuum-induced tamponade exclusively in women with atony.…”
Section: Discussionsupporting
confidence: 89%
“…A subsequent multicenter study of 106 women with uterine atony treated with this device reported a treatment success rate of 94%. 9 The findings of our observational study are in line with these results, showing a success rate of 86% in women with uterine atony in the overall study period and even 100% in women with uterine atony in the latter 2 years. However, in contrast to the latter study, we did not use vacuum-induced tamponade exclusively in women with atony.…”
Section: Discussionsupporting
confidence: 89%
“…90 A novel intra-uterine vacuum-inducing device for control of uterine atony has recently been described. 91…”
Section: Uterine Tamponade Methodsmentioning
confidence: 99%
“…In the trial, eight adverse events were reported as possibly related to the device or procedure, all of which were anticipated with the introduction of an intrauterine device. These events included endometritis (n = 4), presumed endometritis (n = 1), disruption of vaginal laceration repair (n = 1), bacterial vaginosis (n = 1), and vaginal candidiasis (n = 1) [10]. Additionally, there were no reports in the trial of uterine perforation or lower genital tract tissue injury in relation to the device or procedure.…”
Section: Safety and Complicationsmentioning
confidence: 99%